Cardiac NO signalling in the metabolic syndrome. (15th December 2014) - Pechánová, O; Varga, Z V; Cebová, M; Giricz, Z; Pacher, P; Ferdinandy, P
<x xml:space="preserve">Abstract</x> It is well documented that metabolic syndrome (i.e. a group of risk factors, such as abdominal obesity, elevated blood pressure, elevated fasting plasma glucose, high serum triglycerides and low cholesterol level in high‐density lipoprotein), which raises the risk for heart disease and diabetes, is associated with increased reactive oxygen and nitrogen species (ROS/RNS) generation. ROS/RNS can modulate cardiac NO signalling and trigger various adaptive changes in NOS and antioxidant enzyme expressions/activities. While initially these changes may represent protective mechanisms in metabolic syndrome, later with more prolonged oxidative, nitrosative and nitrative stress, these are often exhausted, eventually favouring myocardial RNS generation and decreased NO bioavailability. The increased oxidative and nitrative stress also impairs the NO‐soluble guanylate cyclase (sGC) signalling pathway, limiting the ability of NO to exert its fundamental signalling roles in the heart. Enhanced ROS/RNS generation in the presence of risk factors also facilitates activation of redox‐dependent transcriptional factors such as NF‐κB, promoting myocardial expression of various pro‐inflammatory mediators, and eventually the development of cardiac dysfunction and remodelling. While the dysregulation of NO signalling may interfere with the therapeutic efficacy of conventional drugs used in the management of metabolic syndrome, the modulation of NO signalling may also be responsible for the therapeutic benefits of already proven or recently developed treatment approaches, such as ACE inhibitors, certain β‐blockers, and sGC activators. Better understanding of the above‐mentioned pathological processes may ultimately lead to more successful therapeutic approaches to overcome metabolic syndrome and its pathological consequences in cardiac NO signalling. Linked Articles This article is part of a themed section on Pharmacology of the Gasotransmitters. To view the other articles in this section visit http://dx.doi.org/10.1111/bph.2015.172.issue-6